Pemberdayaan Masyarakat Nelayan dalam Rangka Penanggulangan Kemiskinan di Kabupaten Minahasa Selatan - Arie Frits Kawulur (Jurnal Aplikasi Manajemen, 2010)
This Research aims to find out: Whether is the empowerment of fishermen community which done by government give positive impact to reducing poverty, and how to influence of the empowerment of fishermen community towards reducing poverty in south minahasa regency. This research used quantitative and qualitative descriptive methods and population is all of family are 720 fishermen. Sample is 10 % of 720 fishermen with proportional random sampling. The result of this research showed that the empowerment of fishermen community and reducing powerty in south minahasa regency have positive correlation and significant influence. The empowerment of fishermen program by government gave reducing poverty of fishermen if the fishermen could have managing efficiently and effectively. Fishermen in the group has been increasing the tools of fishermen as "giob" and "pajeko" can increasing his income and reducing the poverty.